2022
DOI: 10.1037/edu0000728
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the boundaries of education research: A multidimensional approach to characterizing preschool neighborhoods and their relations with child outcomes.

Abstract: With more low-income children in the United States participating in center-based early childhood education programs than ever before, understanding the features of preschool classrooms that promote positive and equitable outcomes for children is of increasing concern to education researchers. Relatively little empirical work, however, has considered the role that characteristics outside of preschool walls might play in shaping low-income children’s learning and development early in life. This study uses novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…Results of this study showed consistent evidence that students living in higher-resourced neighborhoods had higher school readiness skills at the start of kindergarten than those in lowerresourced neighborhoods. These results reinforce existing literature relating neighborhood conditions to academic outcomes (Vaden-Kiernan et al, 2010;McCoy et al, 2015) and expand on newer research investigating neighborhoods and early childhood outcomes (Wei et al, 2021;McCoy et al, 2022). Further, while prior research has shown a strong association between children's family income level and children's school readiness skills at kindergarten entry (Isaacs, 2012;Reardon and Portilla, 2016;Latham, 2018), the current study found that utilizing a more comprehensive measure of neighborhood conditions matters for school readiness, as well.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Results of this study showed consistent evidence that students living in higher-resourced neighborhoods had higher school readiness skills at the start of kindergarten than those in lowerresourced neighborhoods. These results reinforce existing literature relating neighborhood conditions to academic outcomes (Vaden-Kiernan et al, 2010;McCoy et al, 2015) and expand on newer research investigating neighborhoods and early childhood outcomes (Wei et al, 2021;McCoy et al, 2022). Further, while prior research has shown a strong association between children's family income level and children's school readiness skills at kindergarten entry (Isaacs, 2012;Reardon and Portilla, 2016;Latham, 2018), the current study found that utilizing a more comprehensive measure of neighborhood conditions matters for school readiness, as well.…”
Section: Discussionsupporting
confidence: 84%
“…Recent research has also found that neighborhoods can provide protective factors for low-income preschoolers. For example, high-resource neighborhoods were associated with gains in children's executive function skills (McCoy et al, 2022), especially in lower income but higherresourced neighborhoods (Wei et al, 2021). These findings suggest that neighborhoods are a key context to explore in considering children's developing school readiness skills.…”
Section: Development Happens In the Context Of Neighborhoodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a handful of studies have explored preschool neighborhood structural characteristics (e.g., McCoy et al, 2015, 2021; Vaden-Kiernan et al, 2010; W. Wei et al, 2021), and even fewer have studied physical characteristics.…”
Section: Need For Measures Of Preschool Communitiesmentioning
confidence: 99%
“…Composite indices of disadvantage have also been used to demonstrate links to children’s stress physiology ( Finegood et al, 2017 ) and to differences in functioning of brain regions underlying self-regulatory processes ( Gard et al, 2021 ). On the one hand, composite indices or profiles capturing co-occurring risks can be highly useful for comparing across different neighborhoods because they condense the complex exposures encompassed by neighborhoods ( Messer et al, 2006 ; McCoy et al, 2022 ). On the other hand, however, understanding the ways in which specific aspects of the built and social environments may influence children’s self-regulation can serve to highlight new opportunities for enriching neighborhood contexts to support the development of self-regulation.…”
Section: Introductionmentioning
confidence: 99%